Pengaruh variasi penambahan jumlah tepung cangkang tiram (Crassostrea gigas) terhadap evaluasi sensori kerupuk - Nurnidar Nurnidar; Lia Handayani; Rulita Maulidya (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study was conducted to determine the effect of oyster shell flour additives on the properties of the cracker organoleptic test. The research method used is the Laboratory experimental method through two stages of making oyster shell flour with NaOH 0.1 N and husk ash, and making crackers with the addition of oyster shell flour is selected as the best of the two flours as ingredients in making crackers. Nonparametric data were analyzed using the Kruskall-Wallis method, the Mann-Whitney test if there was a significant difference, followed by the Bayes test to determine the best treatment. Oyster shell crackers were selected by 30 semi-trained panelists, and the results showed that treatment D (addition of 15% oyster shell flour) resulted in more preferred crackers than other samples, with a taste value of 7.86±0.02, aroma value of 7.71±0.07, texture 7.75±0.07 (crispy), and color 7.79±0.02 (faded yellow, similar to the color of crackers in general).